Implementation of real‐time TDDFT for periodic systems in the open‐source PySCF software package - Hanasaki, Kota; Ali, Zulfikhar A.; Choi, Min; Del Ben, Mauro; Wong, Bryan M. (Journal of computational chemistry, 2023)
We present a new implementation of real‐time time‐dependent density functional theory (RT‐TDDFT) for calculating excited‐state dynamics of periodic systems in the open‐source Python‐based PySCF software package. Our implementation uses Gaussian basis functions in a velocity gauge formalism and can be applied to periodic surfaces, condensed‐phase, and molecular systems. As representative benchmark applications, we present optical absorption calculations of various molecular and bulk systems and a real‐time simulation of field‐induced dynamics of a (ZnO)4 molecular cluster on a periodic graphene sheet. We present representative calculations on optical response of solids to infinitesimal external fields as well as real‐time charge‐transfer dynamics induced by strong pulsed laser fields. Due to the widespread use of the Python language, our RT‐TDDFT implementation can be easily modified and provides a new capability in the PySCF code for real‐time excited‐state calculations of chemical and material systems. Real‐time electron dynamics of (ZnO)4 molecular clusters on a periodic graphene sheet irradiated by an external light source.